ANTI-MELANOMA BIO-EFFICACY OF THE PLANT MADHUCA LONGIFOLIA AND ITS ENHANCEMENT USING BIOACTIVE PRINCIPLE LOADED GOLD NANOPARTICLE - YADAV, SAURABH; SHARMA, MUKTI; GANESH, NARAYANAN; SRIVASTAVA, SHALINI; SRIVASTAVA, M. M. (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Unexplored in-vivo anti-melanoma bio-efficacy of the plant Madhuca longifolia (bark) has been carried out against C57BL/6 mice. Methods: Optimized experimental conditions of phytofabrication of gold nanoparticles were as follows: flavonoid content (1 ml, 0.5 mg/ml), sodium tetrachloroaurate dihydrate solution (2 ml, 1 mM), and sonication (15 min, 20 KHz) at pH 4. The optical properties; ultraviolet-visible spectrophotometer (UV-Vis), particles size and zeta potential (Zetasizer), miller indices; X-ray diffraction (XRD), morphology; field emission-scanning electron microscope (FE-SEM), particle size; high resolution-transmission electron microscopy (HR-TEM), surface roughness; atomic force microscopy (AFM) and elemental composition; and energy dispersive X-rays (EDX) of flavonoid loaded gold nanoparticles. In-vivo anti-melanoma bio-efficacy has been carried out against C57BL mice. Radioisotopic, hematological, and histopathological studies were carried out using standard procedures. Results: Redox potential of the total flavonoid extracted from the bark of the plant (Madhuca longifolia) has been used for the fabrication of flavonoid loaded gold nanoparticles (F@AuNp) and confirmed for the first time their significant anti-melanoma bio-efficacy. The finding is supported by hematological and histopathological studies carried out in the organs (liver, kidney, and intestine) of C57BL mice. The significant enhancement in phytofabricated F@AuNp compared to native bark extract of the plant has been assigned to enhanced stay period and nanosizing, biocompatibility, nontoxic nature, and enhanced beneficial payload to the cancerous cells. Conclusion: Such phytofabricated gold nanoparticles possess an admirable prospect for the expansion of herbal nanomedicine for anti-melanoma bio-efficacy.